The Impact of Online Consumer Reviews, E-Service Quality, and Content Marketing on Purchasing Decisions on the Shopee Seller Marketplace, with Islamic Business Ethics as a Moderation Variable - Hana, Kharis Fadlullah; Miranti, Ajeng Rizki (Universitas Islam Negeri Sunan Kudus, 2021)
Today, there is a lot of interest in Indonesian spending on the market; in 2021, overall Indonesian expenditure on the market climbed by 26%. Shopee is an Indonesian marketplace app with 93,440,300 monthly users. Sellers in the Shopee marketplace, on the other hand, are still learning how to effectively handle the platform. As a result, the goal of this research is to see if OCR (Online Consumer Review), E-Service Quality, and Content Marketing influence purchasing decisions, and if so, whether implementing OCR, E-Service Quality, and Content Marketing with Islamic business ethics strengthens or weakens the influence of purchasing decisions. The quantitative technique was employed in this investigation. Students from IAIN Kudus, UMK, and UMKU who utilize the shopee marketplace are the focus of this study. Because the population in this study was unlimited, researchers utilized the lemeshow method to determine the sample size and acquired 96 research samples. This study employs nonprobability sampling methods using purposive sampling. The data gathering approach is done through disseminating questionnaires. SPSS version 2.3 is used to process the data obtained. Validity tests, reliability tests, statistical tests, and traditional assumption tests are all used in data analysis techniques. The findings of this study revealed that online consumer reviews, e-service quality, and content marketing all influenced purchase decisions on shopee seller marketplaces and MRA tests, indicating that Islamic business ethics is a pure moderator variable that has a positive impact on online consumer reviews, e-service quality, and content marketing.